Construction of the Adjusted Scoliosis 3D Finite Element Model and Biomechanical Analysis under Gravity. Issue 2 (8th December 2022) - Li, Jiahao; An, Zhicheng; Wu, Jigong; Gao, Yongchang; Lu, Sheng; He, Da; Zhao, Yu
Abstract : Objective: Adolescent idiopathic scoliosis (AIS) is a three‐dimensional structural deformity of the spine caused by the disruption of the biomechanical balance of the spine. However, the current biomechanical modeling and analysis methods of scoliosis cannot really describe the real state of the spine. This study aims to propose a high‐precision biomechanical modeling and analysis method that can reflect the spinal state under gravity and provide a theoretical basis for therapeutics. Methods: Combining CT and X‐ray images of AIS patients, this study constructed an adjusted three‐dimensional model and FE model of the spine corresponding to the patient's gravity position, including vertebral bodies, intervertebral discs, ribs, costal cartilage, ligaments, and facet cartilage. Then, the displacement and stress of the spine under gravity were analyzed. Results: A model of the T1‐Sacrum with 1.7 million meshes was constructed. After adding the gravity condition, the maximum displacement point was at T1 of thoracic vertebra (20.4 mm). The analysis indicates that the stress on the lower surface of the vertebral body in thoracolumbar scoliosis tended to be locally concentrated, especially on the concave side of the primary curvature's vertebral body (the maximum stress on the lower surface of T9 is 32.33 MPa) and the convex side of the compensatory curvature's vertebral body (the maximum stress on the lower surface of L5 is 41.97 MPa). Conclusion: This study provides a high‐precision modeling and analysis method for scoliosis with full consideration of gravity. The reliability of the method was verified based on patient data. This model can be used to analyze the biomechanical characteristics of patients in the treatment plan design stage. Abstract : In this study, a model adjustment method based on X‐ray images was proposed to simulate the biomechanics of scoliosis patients under gravity. This model is more consistent with the patient's physiological status and can be used as a planning basis for scoliosis patients before treatment.